IDEOLOGICAL THREATS AND THE PROBLEM OF SOCIAL STABILITY IN THE 21ST CENTURY - Mukhitdinova Iroda Makhmudkhanovna (Sciental Journals Publishing, 2025)
This article analyzes ideological threats and the problem of social stability in the 21st century. It emphasizes the growing importance of spiritual struggle and ideological security in contemporary global processes, as well as the intensification of ideological threats that distort the consciousness of the younger generation. The paper examines the concepts of ideological struggle, ideological confrontation, and spiritual threats, their impact on social stability, and scientific perspectives on preventive measures.
Keywords: Ideological threat, spiritual security, social stability, ideological struggle, youth, globalization, spiritual immunity.